Antimicrobial Resistance Patterns of Staphylococcus aureus Cultured from the Healthy Horses’ Nostrils Sampled in Distant Regions of Brazil - Mauro M. S. Saraiva; Heitor Leocádio de Souza Rodrigues; Valdinete Pereira Benevides; Candice Maria Cardoso Gomes de Leon; Silvana C. L. Santos; Danilo T. Stipp; Patricia E. N. Givisiez; Rafael F. C. Vieira; Celso J. B. Oliveira (Antibiotics, 2025)
Staphylococcus aureus (S. aureus) is a major cause of opportunistic infections in humans and animals, leading to severe systemic diseases. The rise of MDR strains associated with animal carriage poses significant health challenges, underscoring the need to investigate animal-derived S. aureus. Objectives: This study examined the genotypic relatedness and phenotypic profiles of antimicrobial resistance in S. aureus, previously sampled from nostril swabs of healthy horses from two geographically distant Brazilian states (Northeast and South), separated by over 3700 km. The study also sought to confirm the presence of methicillin-resistant (MRSA) and borderline oxacillin-resistant (BORSA) strains and to characterize the isolates through molecular typing using PCR. Methods: Among 123 screened staphylococci, 21 isolates were confirmed as S. aureus via biochemical tests and PCR targeting species-specific genes (femA, nuc, coa). Results: REP-PCR analysis generated genotypic profiles, revealing four antimicrobial resistance patterns, with MDR observed in ten isolates. Six isolates exhibited cefoxitin resistance, suggesting methicillin resistance, despite the absence of the mecA gene. REP-PCR demonstrated high discriminatory power, grouping the isolates into five major clusters. Conclusions: The genotyping indicated no clustering by geographical origin, highlighting significant genetic diversity among S. aureus strains colonizing horses’ nostrils in Brazil. These findings highlight the widespread and varied nature of S. aureus among horses, contributing to a deeper understanding of its epidemiology and resistance profiles in animals across diverse regions. Ultimately, this genetic diversity can pose a public health risk that the epidemiological surveillance services must investigate.